2019
DOI: 10.17239/jowr-2019.11.02.03
|View full text |Cite
|
Sign up to set email alerts
|

Same goal, different beliefs: Students’ preferences and teachers’ perceptions of feedback on second language writing

Abstract: value of f Moreover, bridge the program source, m regarded t in their w attitudes t correction tone; (4) w both rheto neutral ab are offered Keywords Wu, S. (2019). S ess of feedback 7239/jowr-2019 Qiandi Liu, Univ USA -Qiandi.Liu t: Earli | This arti ative Works 3.0 Part 2. All of the sentences below have a grammar error. Please circle the type of corrective feedback that you think as most helpful. 1. The children go skatting in the winter. A. The children go skatting in the winter. B. The children go skattin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 45 publications
(92 reference statements)
1
20
2
Order By: Relevance
“…The teachers also perceived that feedback provided can be done either directly or indirectly. However, more teachers perceived that indirect feedback is more effective to improve the quality of students' writing compared to direct feedback in which it is similar to the previous research findings [29]. In addition, they also had perspectives that correcting students' writing errors was given by indicating the erroneous parts using a particular codes or marks in which they must be easily followed and understood.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The teachers also perceived that feedback provided can be done either directly or indirectly. However, more teachers perceived that indirect feedback is more effective to improve the quality of students' writing compared to direct feedback in which it is similar to the previous research findings [29]. In addition, they also had perspectives that correcting students' writing errors was given by indicating the erroneous parts using a particular codes or marks in which they must be easily followed and understood.…”
Section: Discussionsupporting
confidence: 74%
“…It means that feedback is provided selectively. It is as supported by Liu and Wu [29]. The teachers also perceived that feedback provided can be done either directly or indirectly.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…By presenting the participants with identical questions regarding L2 writing in two distinct methods (i.e., agreement and ranking), the results present a more complete picture of where instructors and students overlap. It is this two-pronged approach that likely explains why the current set of results diverges from previous work in asserting that instructors and students are generally aligned in their opinions and beliefs (across the majority of the ranking data), while simultaneously supporting some aspects of previous findings (within the more fine-tuned agreement data, e.g., Brown, 2009;Liu & Wu, 2019;Schulz, 1996Schulz, , 2001.…”
Section: (22)contrasting
confidence: 60%
“…A more recent study examining student and instructor opinions about corrective feedback on writing assignments (Liu & Wu, 2019) similarly found that students and instructors agreed about some aspects of corrective feedback (e.g., the utility of oral feedback, the utility of rhetorical and language‐centered feedback and the helpfulness of providing both positive and negative feedback on assignments) and disagreed about others (e.g., instructors found peer review less helpful than students, they did not find it necessary to correct every error they encountered and they were more likely to view indirect feedback as important). Therefore, regardless of how a particular curriculum incorporates explicit grammar instruction or error correction, for example, it is essential for the curriculum designers to know that whatever choice is made will have a distinct impression on learners and instructors.…”
Section: Review Of Literaturementioning
confidence: 99%